2020
DOI: 10.14256/jce.2568.2018
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of nano ulexite mineral effects on mechanical behaviour of warm mix asphalt pavements

Abstract: Investigation of nano ulexite mineral effects on mechanical behaviour of warm mix asphalt pavements Research paper Tuba Kütük-Sert, Resul Ekrem Günbey Investigation of nano ulexite mineral effects on mechanical behaviour of warm mix asphalt pavements The research presented in the paper shows that further investigations on additives used in the warm mix asphalt technology are needed. It was observed that the negative effect of adhesion loss in asphalt mixes produced by warm process can be reduced by adding ulex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Different synthetic products have been created to reduce environmental impacts when paving road works, and other natural products have been reappraised that can reduce the manufacturing and laying temperature of asphalt mixes. This has generated warm mix asphalts (WMA), which reduce polluting gas emissions and the energy needed to produce the mix and pavement construction processes [5][6][7]. Additionally, studies have demonstrated the technical effectiveness of incorporating recycled asphalt pavement (RAP) compared to traditional hot mix asphalt (HMA) in promoting recycled material use.…”
Section: Introductionmentioning
confidence: 99%
“…Different synthetic products have been created to reduce environmental impacts when paving road works, and other natural products have been reappraised that can reduce the manufacturing and laying temperature of asphalt mixes. This has generated warm mix asphalts (WMA), which reduce polluting gas emissions and the energy needed to produce the mix and pavement construction processes [5][6][7]. Additionally, studies have demonstrated the technical effectiveness of incorporating recycled asphalt pavement (RAP) compared to traditional hot mix asphalt (HMA) in promoting recycled material use.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the design of highway networks that requires large capital expenditures is very important [1,2]. A satisfactory pavement design should be sufficiently serviceable, durable, resistant to permanent deformation, economical, and eco-friendly [3][4][5]. On a global scale, flexible pavements are the preferred type of highway superstructure [6][7][8].…”
Section: Introductionmentioning
confidence: 99%